‘Wrighting And Archiving’: Lessons Learned By A Survivor Of Rape By A ‘Holy’ Monk - Khunphakdee, Manee (2016)
“It only remained for me to give it voice, to shared it for use, that the pain not be wasted.” (Lorde,1997,p.14) As a Women’s NGO worker and recently a student in the MA program of Women, Gender and Sexuality Studies, I’d like to share the story of Oy, a girl who had been raped by a ‘holy’ monk for many years. The process of finding her own language, standing up and speaking out was not an easy process as there were many layers of unequal power between the girl and the man, an ordinary person and monk. In particular, for the latter, he had performed and was perceived as a ‘holy body’ who not only gave fortune to the villagers but also saved them from bad luck and illness through many different techniques. The girl started her story by writing petitions to the Religion Administrative Unit at both the district and provincial levels. Instead, the monk was protected by his institution. Finally, she brought her case to court along with her archive. My study of her writings and archiving process will be shared and discussed within the framework of feminist writing elaborated by Lorde and Trinh Minh Ha, respectively.